Current treatments in the management of patients with primary hyperparathyroidism. Issue 999 (24th February 2009) - Iglesias, P; Díez, J J
Abstract : Primary hyperparathyroidism (PHP) develops as a consequence of autonomous hypersecretion of parathyroid hormone (PTH) by parathyroid glands usually because of a solitary parathyroid adenoma. Parathyroidectomy, a surgical procedure with a high success rate, is currently the treatment of choice. Pathological parathyroid tissue excision can be achieved by surgical and non-surgical ablative therapy. Bilateral cervical surgical exploration performed by an experienced parathyroid surgeon is curative in 95–98% of PHP and is associated with a low complication rate. In some patients, such as those with a single parathyroid adenoma adequately localised in presurgical imaging studies, this type of surgery may be more extensive than is needed. Moreover, the introduction of new intraoperative parathyroid-localising techniques, such as intraoperative PTH measurement and nuclear mapping, has boosted the development of new and less invasive parathyroid surgical techniques. Other non-surgical ablative techniques, such as selective percutaneous ethanol injection and transcatheter ablation of pathological parathyroid tissue, may be adequate in cases in which surgery is contraindicated. Lastly, among the therapeutic alternatives to parathyroidectomy are antiresorptive drugs (bisphosphonates, oestrogens and selective oestrogen receptor modulators) and inhibitors of PTH secretion (calcimimetics). A combination of drugs with diverse mechanisms of action may have a synergistic effect in the symptomatic control of PHP.